DIFFUSION OF INNOVATION IN DISTRICT INTEGRATED ADMINISTRATION SERVICES (PATEN) IN REALIZING GOOD GOVERNANCE IN BIRINGKANAYA DISTRICT, MAKASSAR CITY - Andi Nur Khadijah; Novayanti Sopia Rukmana; Sulmiah Sulmiah (Universitas Negeri Makassar, 2026)
This study aims to find out how the Diffusion of Innovation in Integrated District Administrative Services (PATEN) in realizing Good Governance in Biringkanaya District, Makassar City. This type of research is descriptive with a qualitative approach. The data collection techniques used are observation, interviews, and documentation. The data analysis technique uses interactive methods, namely data condensation, data presentation, and conclusion drawn. The results of the study show that the diffusion of patent innovations in Biringkanaya District, Makassar City has not been optimally adopted. This refers to the four main elements in innovation diffusion, which among the four main elements of innovation diffusion there are three elements that are included in the poor category, namely innovation elements that are still found to have some weaknesses from before the implementation of the PATENT innovation, communication channel elements that are still not effective in the use of communication channels because they only use interpersonal communication, and time period elements that are classified as slow, especially during the trial period Adoption. In addition, there is one element of diffusion that is included in the good category, namely the element of the social system with the results of the research finding that the target and role of the leader are effective in adopting PATENT innovations. In this study, it is suggested that the government that diffuses or adopts innovations is expected not only to follow the demands of the rules, but also to be balanced with the readiness of the organizers both in terms of infrastructure and human resources.